Mengulik Pemahaman tentang Gender menurut Kejadian 1:27 sebagai Refleksi Teologi Pentakosta Tradisional terhadap LGBT - Purnomo, Catur Sigit; Manurung, Kosma (Sekolah Tinggi Teologi Transformasi Indonesia, 2023)
Abstract: In this post-modern era, the issue of gender has become increasingly complex. Within Christianity itself, there is a debate about whether the gender issue can be tolerated and accepted within a religious context or not. Churches also tend to differ in their implementation of policies related to this issue, ranging from rejection, indifference, to acceptance. From this dilemma, it is interesting to understand how Pentecostals, in particular, view this matter. This article seeks to examine how the Bible, especially Genesis 1:27, perceives the concept of gender and how this perspective can be applied to LGBT individuals from a Pentecostal standpoint. Through textual analysis and careful literature review, this article investigates the Bible's viewpoint on the LGBT community and offers an interpretation in the form of a divine gender concept according to the Bible. The Pentecostal reflection found includes an emphasis on gender, sexual organs in relation to the divine reproductive system, the holiness of a believer's life, and the need for a divine community to provide support in implementing the divine gender concept in a holistic manner.Abstrak: Pada zaman post-modern ini, isu mengenai gender menjadi semakin rumit. Dalam Kekristenan sendiri, terdapat pertentangan apakah isu mengenai gender ini dapat ditoleransi dan diterima dalam konteks keagamaan atau tidak. Gereja pun cenderung berbeda dalam menerapkan kebijakan terkait isu ini, mulai dari yang menolak, mengabaikan hingga menerima. Dari dilema ini, maka menarik untuk memahami bagaimana kaum Pentakostal, menilik hal ini. Artikel ini berupaya mengkaji bagaimana Alkitab, terutama kitab Kejadian 1:27, memandang konsep gender dan bagaimana pandangan ini dapat diterapkan pada orang-orang LGBT dari sudut pandang kaum Pentakostal. Menerapkan analisis teks serta menggunakan kajian literatur secara seksama, artikel ini menyelidiki cara pandang Alkitab terhadap komunitas LGBT dan membuat interpretasi berupa konsep gender yang ilahi menurut Alkitab. Refleksi Pentakostal yang ditemukan mencakup penekanan pada gender, organ seksual dalam hubungannya dengan sistem reproduksi ilahi, kesucian hidup orang percaya, serta perlunya komunitas yang ilahi untuk memberikan dukungan dalam rangka menerapkan konsep gender yang Ilahi secara holistik.